Broad frequency band full field measurements for advanced applications: Point-wise comparisons between optical technologies. (1st January 2018) - Zanarini, Alessandro
Highlights: Optical instruments tested to estimate FRF & Coherence in plate structural dynamics. Point-wise comparative procedure to assess the quality of results in the same points. High spatial resolution for experimental patterns of rotational & dynamic strain FRFs. Experimental dynamic & equivalent Von Mises stress FRFs for fatigue life assessment. Experimental Full Field Modal Analysis & Model Updating: high resolution & continuity of shapes. Abstract: The progress of optical systems gives nowadays at disposal on lightweight structures complex dynamic measurements and modal tests, each with its own advantages, drawbacks and preferred usage domains. It is thus more easy than before to obtain highly spatially defined vibration patterns for many applications in vibration engineering, testing and general product development. The potential of three completely different technologies is here benchmarked on a common test rig and advanced applications. SLDV, dynamic ESPI and hi-speed DIC are here first deployed in a complex and unique test on the estimation of FRFs with high spatial accuracy from a thin vibrating plate. The latter exhibits a broad band dynamics and high modal density in the common frequency domain where the techniques can find an operative intersection. A peculiar point-wise comparison is here addressed by means of discrete geometry transforms to put all the three technologies on trial at each physical point of the surface. Full field measurement technologies cannot estimate only displacement fields on a refined grid, but can exploit the spatial consistency of the results through neighbouring locations by means of numerical differentiation operators in the spatial domain to obtain rotational degrees of freedom and superficial dynamic strain distributions, with enhanced quality, compared to other technologies in literature. Approaching the task with the aid of superior quality receptance maps from the three different full field gears, this work calculates and compares rotational and dynamic strain FRFs. Dynamic stress FRFs can be modelled directly from the latter, by means of a constitutive model, avoiding the costly and time-consuming steps of building and tuning a numerical dynamic model of a flexible component or a structure in real life conditions. Once dynamic stress FRFs are obtained, spectral fatigue approaches can try to predict the life of a component in many excitation conditions. Different spectral shaping of the excitation can easily be used to enhance the comparison in the framework of any of the spectral approaches for fatigue life calculations, highlighting benefits and drawbacks of a direct experimental approach to failure and risk assessment in structural dynamics when dealing with complex patterns in real-life testing. Are optical measurements and spatially dense datasets really effective in advanced model updating of lightweight structures with complex structural dynamics? The noise shown in the raw signal of some experiments may pose issues in proficiently exploiting the added data in a fruitful model updating procedure. Model updating results are here compared between scanning and native full field technologies, with comments and details on the test rig, on the advantages and drawbacks of the approaches. The identification of EMA models highlights the increasing quality of shapes that can be obtained from native full field high resolution gears, against that (some time unexpectedly poor) of SLDV tested.